2012
DOI: 10.2165/11598470-000000000-00000
|View full text |Cite|
|
Sign up to set email alerts
|

Cost Effectiveness of Oromucosal Cannabis-Based Medicine (Sativex®) for Spasticity in Multiple Sclerosis

Abstract: Using a willingness-to-pay threshold of £30 000 per QALY, Sativex® appears unlikely to be considered cost effective by UK funders of healthcare for spasticity in MS. This is unfortunate, since it appears that Sativex® use is likely to benefit some patients in the management of this common consequence of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…The observation that patient, caregiver and physician-reported efficacy was maintained over the 12-month period suggests that the maintenance of efficacy can be achieved at lower drug exposures that are seen in short-term clinical trials, and confirms previous observations that there is no evidence of tolerance with continuing use [10]. It also seems likely to have some implications for the pharmaco-economic evaluation of the cost-benefit of Sativex, which is generally based on a daily dose of eight sprays [32].…”
Section: Discussionsupporting
confidence: 78%
“…The observation that patient, caregiver and physician-reported efficacy was maintained over the 12-month period suggests that the maintenance of efficacy can be achieved at lower drug exposures that are seen in short-term clinical trials, and confirms previous observations that there is no evidence of tolerance with continuing use [10]. It also seems likely to have some implications for the pharmaco-economic evaluation of the cost-benefit of Sativex, which is generally based on a daily dose of eight sprays [32].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, cost-effectiveness analyses from Germany/Spain [28] and Italy [29] have shown that, compared with current standard-of-care treatment (physiotherapy and oral antispasticity medications) for patients with resistant MS-related spasticity, Sativex add-on therapy is a cost-effective option at commonly accepted willingness-to-pay thresholds. Although a similar cost-effectiveness analysis from the UK failed to replicate these results [30], differences in the way in which the Markov model was constructed (e.g., a higher mean dose of Sativex) might have contributed to a less favorable conclusion.…”
Section: Discussionmentioning
confidence: 95%
“…A publicly funded study in the United Kingdom found that nabiximols were not cost-effective at that threshold, while industry-funded studies built using Spain, Germany, Italy, and Wales as health marketplace settings found nabiximols to be cost-effective. 43–46…”
Section: Discussionmentioning
confidence: 99%